Kajian kinerja pertumbuhan dan kelangsungan hidup ikan kerapu macan (Ephinephelus fuscogusttatus) menggunakan pakan hewani yang berbeda - Khalil, Munawwar; Salamah, Salamah; Zumairi, Zumairi; Muliani, Muliani (Acta Aquatica: Aquatic Sciences Journal, 2021)
The tiger grouper (Epinephelus fuscoguttatus) is an economically important fish whose fry still relies on natural catches. Several species of grouper are very potential to be cultivated because of their fast growth, efficient feed conversion, and high selling value. The purpose of this study is growth performance and survival rate tiger grouper (Epinephelus fuscoguttatus) used different live feed. The research design used in this study was a Completely Randomized Design with 3 treatments 3 replications and continued with LSD test if there were differences. The treatments given are treatment A (Snail), treatment B (Chicken Intestine), and treatment C (Caterpillar Maggot). Parameters observed were length increase, weight gain, survival, feed response, and water quality. The results of this study indicate that the highest increase was found in the treatment of C: 4,04 cm and the lowest was in treatment B: 3 cm, the highest weight gain was found in the treatment of C: 3,73 grams, and the lowest was in treatment B: 2,18 grams. The survival rate for all treatments is 100%. During this study the temperature ranged (28.6-31.8 oC), pH (6.7-8.2), DO (6.3-8.1 ppm), and salinity (23-27 ppt).Keywords: growth, live feed, survival rate, tiger grouper.